A case report of uterine leiomyosarcoma - Kirubanandan, Sandhiya; Jaget, Nirmala; Sekar, Sindhuja; Saranya, Sri; R., Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The most prevalent benign tumour in women is uterine leiomyoma. Smooth muscle cells give rise to the uncommon malignant tumour known as uterine leiomyosarcoma. It makes up 1% of all uterine cancers. One out of every 800 women who are thought to have leiomyoma actually has a sarcoma. Uterine leiomyosarcoma is usually diagnosed by histopathological examination and surgery is the only treatment. We describe a 48-year-old woman who had heavy menstrual flow and was initially diagnosed with uterine leiomyoma. Histological analysis revealed that she actually had uterine leiomyosarcoma.